Characterization Performance of Monocrystalline Silicon Photovoltaic Module Using Experimentally Measured Data (Journal of Engineering, 2019)
Solar photovoltaic (PV) system has emerged as one of the most promising technology to generate clean energy. In this work, the performance of monocrystalline silicon photovoltaic module is studied through observing the effect of necessary parameters: solar irradiation and ambient temperature. The single diode model with series resistors is selected to find the characterization of current-voltage (I-V) and power-voltage (P-V) curves by determining the values of five parameters ( ). This model shows a high accuracy in modeling the solar PV module under various weather conditions. The modeling is simulated via using MATLAB/Simulink software. The performance of the selected solar PV module is tested experimentally for different weather data (solar irradiance and ambient temperature) that is gathered from October 2017 to April 2018 in the city of Baghdad. The collected data is recorded for the entire months during the time which is limited between 8:00 AM and 1:00 PM. This work demonstrates that the change in a cell temperature is directly proportional with the PV module current, while it is inversely proportional with the PV module voltage. Additionally, the output power of a PV module increases with decreasing the solar module temperature. Furthermore, the Simulink block diagram is used to evaluate the influence of weather factors on the PV module temperature by connecting to the MATLAB code. The best value from the results of this work was in March when the solar irradiance was equal to 1000 W/m2 and the results were:Isc,exp=3.015, Isc,mod=3.25 , RE=7.79 and Voc,exp=19.67 ,Voc,mod=19.9 ,RE=1.1